Modeling and forecasting abnormal stock returns using the nonlinear Grey Bernoulli model - Doryab, Bahar; Salehi, Mahdi (Universidad ESAN. ESAN Ediciones, 2018)
Purpose – This study aims to use gray models to predict abnormal stock returns. Design/methodology/approach – Data are collected from listed companies in the Tehran Stock Exchange during 2005-2015. The analyses portray three models, namely, the gray model, the nonlinear gray Bernoulli model and the Nash nonlinear gray Bernoulli model. Findings – Results show that the Nash nonlinear gray Bernoulli model can predict abnormal stock returns that are defined by conditions other than gray models which predict increases, and then after checking regression models, the Bernoulli regression model is defined, which gives higher accuracy and fewer errors than the other two models. Originality/value – The stock market is one of the most important markets, which is influenced by several factors. Thus, accurate and reliable techniques are necessary to help investors and consumers find detailed and exact ways to predict the stock market.

Propósito – Este estudio tiene como objetivo utilizar modelos grises para predecir rendimientos anormales de acciones. Diseño / metodología / enfoque – Los datos se recopilan de empresas que cotizan en la Bolsa de Valores de Teherán durante 2005-2015. Los análisis muestran tres modelos, a saber, el modelo gris, el modelo Bernoulli gris no lineal y el modelo Bernoulli gris no lineal de Nash. Recomendaciones – Los resultados muestran que el modelo de Bernoulli gris no lineal de Nash puede predecir rendimientos de acciones anormales que se definen por condiciones distintas de los modelos grises que predicen aumentos, y luego, después de verificar los modelos de regresión, se define el modelo de regresión de Bernoulli, que proporciona una mayor precisión y menos errores que el modelo de regresión de Bernoulli. otros dos modelos. Originalidad / valor – El mercado de valores es uno de los mercados más importantes, en el que influyen varios factores. Por lo tanto, se necesitan técnicas precisas y confiables para ayudar a los inversores y consumidores a encontrar formas detalladas y exactas de predecir el mercado de valores.
Keywords: Abnormal returns; Gray theory; Rendimientos anormales; Nash nonlinear gray Bernoulli model; Teoría de Gray; Modelo Bernoulli gris no lineal de Nash; Nonlinear gray Bernoulli model; Modelo Bernoulli gris no lineal; https://purl.org/pe-repo/ocde/ford#5.02.04